2019
DOI: 10.2219/rtriqr.60.4_256
|View full text |Cite
|
Sign up to set email alerts
|

<b>Fault Detection for Railway Traction Motor Bearing through Leakage Current</b>

Abstract: Much research on detecting machinery faults in the early stage is being conducted for the purpose of preventing failure and reducing maintenance effort simultaneously. In this paper, a bearing fault detection method for a railway traction motor through leakage currents is proposed. The proposed detection method combines octave band analysis and machine learning. Experiments simulating abnormalities due to defective bearings were conducted and the effectiveness of the proposed method was verified. These experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Results of anomaly simulation tests confirmed that an anomaly could be detected in a high-frequency band regardless of the concentration of foreign bodies, and that an anomaly could be detected regardless of the vibration measurement point [18]. Another case study is the anomaly diagnosis of traction motor bearings, where it was confirmed in stationary tests after applying to the leakage current of traction motors instead of bearing vibration that anomalies in bearings could be detected under specific no-load conditions [19].…”
Section: Anomaly Detection Methodsmentioning
confidence: 94%
“…Results of anomaly simulation tests confirmed that an anomaly could be detected in a high-frequency band regardless of the concentration of foreign bodies, and that an anomaly could be detected regardless of the vibration measurement point [18]. Another case study is the anomaly diagnosis of traction motor bearings, where it was confirmed in stationary tests after applying to the leakage current of traction motors instead of bearing vibration that anomalies in bearings could be detected under specific no-load conditions [19].…”
Section: Anomaly Detection Methodsmentioning
confidence: 94%
“…To prevent this, the traction motor fault detection system tracks the frequency of the traction motor using a phase-locked loop. Voltage and current signals are obtained by light sensor, converted into square wave signals by zerocrossing voltage comparator, output square wave signals by phase-locked loop function module, and trigger converter to obtain digital signals [24][25].…”
Section: Phase Locked Loop Modulementioning
confidence: 99%
“…It is of great significance to ensure that the traction motor is free from accidents. However, the safe operation of the traction motor is seriously threatened by the heavy work condition and complex structure [1]. It has been found that almost half of motor failures originate from bearings [2].…”
Section: Introductionmentioning
confidence: 99%